Finite Dimensional Repetitive Controller for Single Phase PWM Inverter - Islam, S; Choudhary, A; Mondal, U (International Journal of Computer Sciences and Engineering, 2025)
In this paper, a finite dimensional repetitive controller (FDRC) scheme is proposed to improve the performance of the output voltage of single phase two level sinusoidal pulse width modulated (PWM) inverter. A single phase two level SPWM inverter model is designed in simulation which provides the provision of deploying different control methods for comparing their sinusoidal tracking performance. Conventional PID controller and then FDRC have been incorporated in the SPWM inverter model and simulated their tracking performances. Comparison is carried out to show advantage, disadvantage or limitation of applied control schemes over conventional PID controller.